1998
DOI: 10.1086/311518
|View full text |Cite
|
Sign up to set email alerts
|

The Declined Activity in the Nucleus of NGC 1316

Abstract: NGC 1316 (Fornax A) is a radio galaxy with prototypical double lobes, where the magnetic field intensity is accurately measured via the inverse Compton technique. The radio-emitting electrons in the lobes are inferred to have a synchrotron lifetime of ∼0.1 Gyr. Considering the lobe energetics, we estimate the past nuclear X-ray luminosity of NGC 1316 to be at least ∼ W ( ergs s Ϫ1 ). Thus, the nucleus was rather active at 34 41 4 # 10 4 # 10 least 0.1 Gyr ago. In contrast, we confirmed with ASCA and ROSAT that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…The obtained X-ray image shows the diffuse X-ray distribution associated to the radio lobe, but we see no significant trend along the jet axis. This supports that the lobe is dormant or inactive as suggested by Iyomoto et al (1998) and Kim & Fabbiano (2003). Considering these evidences of inactivity of jets, we assume a concentric energy distribution below.…”
Section: Observations and Resultssupporting
confidence: 77%
“…The obtained X-ray image shows the diffuse X-ray distribution associated to the radio lobe, but we see no significant trend along the jet axis. This supports that the lobe is dormant or inactive as suggested by Iyomoto et al (1998) and Kim & Fabbiano (2003). Considering these evidences of inactivity of jets, we assume a concentric energy distribution below.…”
Section: Observations and Resultssupporting
confidence: 77%
“…These lobes have allowed a successful detection of inverse Compton X-rays (Feigelson et al 1995;Kaneda et al 1995), providing a reliable estimate of the magnetic field and synchrotron lifetime in the lobes. Iyomoto et al (1998) have reported no significant X-ray emission from the low-luminosity AGN (LLAGN) in the center of the galaxy, which is consistent with the extreme faintness of the radio core. They have concluded that the AGN activity turned off 0.1 Gyr ago from the estimate of the lobe lifetime and the observed radio nucleus versus bridge offset.…”
Section: Resultsmentioning
confidence: 73%
“…The nuclear activity of NGC 1316, however, has decreased markedly over the last 0.1 Gyr and is thus unlikely to be still a direct excitation source of the unusual PAH emission, whereas it might have significantly modified the size distribution of PAHs 0.1 Gyr ago. The galaxy is known to have a hot plasma typical of the ISM of elliptical galaxies (Iyomoto et al 1998). Hence the PAHs exposed to such hot plasma are expected to be under sputtering destruction against plasma ions; the absence of the 3.3 mm PAH emission supports that small PAHs have been destroyed through sputtering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray spectral properties of LLAGNs, particularly LINERs, have most thoroughly been investigated using ASCA (Yaqoob et al 1995;Ishisaki et al 1996;Iyomoto et al 1996Iyomoto et al , 1997Iyomoto et al , 1998aIyomoto et al , 1998bPtak et al 1996Ptak et al , 1999Terashima et al 1998aTerashima et al , 1998bTerashima et al , 2000aTerashima et al , 2000bTerashima et al , 2002Ho et al 1999a;Terashima, Ho & Ptak 2000;Roberts, Schurch & Warwick 2001), with important contributions from BeppoSAX (Pellegrini et al 2000a(Pellegrini et al , 2000b(Pellegrini et al , 2002Iyomoto et al 2001;Georgantopoulos et al 2002;Ptak et al 2004). A seminal study on M81 was done using BBXRT (Petre et al 1993).…”
Section: X-ray Coresmentioning
confidence: 99%